ナンキョク リュツォ・ホルム ワン ノ ユウヒカク ユウリンペン ゲンセイ セイブツ I. テイチャク ヒョウイキ サン ノ エリ ベンモウチュウ ト タイヨウチュウ - 高橋, 永治; タカハシ, エイジ; Takahashi, Eiji (1981)
P(論文) 1981年1月, 観測船「ふじ」の停止点近くの定着氷上(厚さ173cm)の1点(69°06. 75'S, 37°24.6'E)を選び, 径9cmの氷柱とその下の海水(深度約160m)12層から, エリ鞭毛虫のAcanthoecidae科所属の2新種, 6既知種と7未同定種, 太陽虫のCentrohelida所属の1既知種と1未同定種, その他不明種の剌鱗片を見出した。2新種, Parvicorbicula ongulensisとSaepicula leadbeateriと命名された。エリ鞭毛虫の5種はウェッデル海にも産する。そのうちの1種と2新種以外の南極海産の8既知種は, 北極海, 北大西洋, 地中海, カリフォルニア沿岸, ケープタウン沿岸, ニュージーランド, 日本などに広く分布する。また垂直的には, 海氷の下半分から海水100m層まで分布し, 海氷底部と海水10m層の2層に密度が高かった。その被殼数は珪藻殼の10%程度であるが, 本海氷域における亜優占生物群であった。 By means of an electron microscopical study, two new species, six known species and seven forms of unidentified loricae of the Acanthoecidae (Choanoflagellida), two species of the Centrohelida (Heliozoa), and a type of spine scales of unknown taxon were found in the sea ice and sea water at a sampling site selected on the fast ice near the last mooring point (69°06.75'S, 37°24.6'E) of Icebreaker FUJI in Lutzow-Holm Bay, Antarctica, in the 1979-1980 season. Two new species were named Parvicorbicula ongulensis and Saepicula leadbeateri. However, most of species dealt with in the present paper are distributed widely in the Northern Hemisphere. The species collected were distributed in the lower half part of the sea ice and in the water column from just beneath the ice to the 100 meters deep layer. departmental bulletin paper